2021
DOI: 10.1038/s42003-021-02528-w
|View full text |Cite
|
Sign up to set email alerts
|

Modified N-linked glycosylation status predicts trafficking defective human Piezo1 channel mutations

Abstract: Mechanosensitive channels are integral membrane proteins that sense mechanical stimuli. Like most plasma membrane ion channel proteins they must pass through biosynthetic quality control in the endoplasmic reticulum that results in them reaching their destination at the plasma membrane. Here we show that N-linked glycosylation of two highly conserved asparagine residues in the ‘cap’ region of mechanosensitive Piezo1 channels are necessary for the mature protein to reach the plasma membrane. Both mutation of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Polyclonal rabbit and monoclonal mouse anti-Piezo1 was from Novus Biologicals (NBP1-78446 and NBP2-75617); both have been validated by Piezo1 knockdown/knockoff experiments ( 15 , 78 ). For all Piezo1 localization quantifications, the monoclonal NBP2-75617 antibody was used.…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal rabbit and monoclonal mouse anti-Piezo1 was from Novus Biologicals (NBP1-78446 and NBP2-75617); both have been validated by Piezo1 knockdown/knockoff experiments ( 15 , 78 ). For all Piezo1 localization quantifications, the monoclonal NBP2-75617 antibody was used.…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal Rabbit and monoclonal mouse anti-Piezo1 was from Novus Biologicals (NBP1-78446, NBP2- 75617), both have been validated by Piezo1 knock down/knock off experiments( 15, 75 ). For all Piezo1 localization quantifications, the monoclonal NBP2-75617 antibody was used.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, other mechanisms may contribute to shearing force-induced ENaC activation. Notably, Li et al (2021) indicated that the status of N-linked glycosylated PIEZO1 is critical for membrane trafficking. The N-glycan of PIEZO1 may interact with other membrane proteins or the ECM molecules, which suggests an extra ECM-modulating mechanism to regulate mechanosensitivity.…”
Section: The Role Of Ecm In the Force-from-tether Modelmentioning
confidence: 99%